Interplay between two RND systems mediating antimicrobial resistance in brucella suis - Martin, F.A. (2009)
The RND-type efflux pumps are responsible for the multidrug resistance phenotype observed in many clinically relevant species. Also, RND pumps have been implicated in physiological processes, with roles in the virulence mechanisms of several pathogenic bacteria. We have previously shown that the BepC outer membrane factor of Brucella suis is involved in the efflux of diverse drugs, probably as part of a tripartite complex with an inner membrane translocase. In the present work, we characterize two membrane fusion protein-RND translocases of B. suis encoded by the bepDE and bepFG loci. MIC assays showed that the B. suis AbepE mutant was more sensitive to deoxycholate (DOC), ethidium bromide, and crystal violet. Furthermore, multicopy bepDE increased resistance to DOC and crystal violet and also to other drugs, including ampicillin, norfloxacin, ciprofloxacin, tetracycline, and doxycycline. In contrast to the ΔbepE mutant, the resistance profile of B. suis remained unaltered when the other RND gene (bepG) was deleted. However, the ΔbepE ΔbepG double mutant showed a more severe phenotype than the ΔbepE mutant, indicating that BepFG also contributes to drug resistance. An open reading frame (bepR) coding for a putative regulatory protein of the TetR family was found upstream of the bepDE locus. BepR strongly repressed the activity of the bepDE promoter, but DOC released the repression mediated by BepR. A clear induction of the bepFG promoter activity was observed only in the BepDE-defective mutant, indicating a regulatory interplay between the two RND efflux pumps. Although only the BepFG-defective mutant showed a moderate attenuation in model cells, the activities of both bepDE and bepFG promoters were induced in the intracellular environment of HeLa cells. Our results show that B. suis harbors two functional RND efflux pumps that may contribute to virulence. Copyright © 2009, American Society for Microbiology. All Rights Reserved.